A single-center clinical experience with fully percutaneous, minimally invasive fetoscopic surgery for spina bifida aperta - Brawura Biskupski Samaha, Robert; Wielgoś, Mirosław; Kohl, Thomas; Lipa, Michal; Goławski, Ksawery; Kosińska-Kaczyńska, Katarzyna; Luterek, Katarzyna; Kosiński, Przemysław; Sienczyk, Julia (Biomedicines, 2025)
Background/Objectives: Following a tailored curriculum, minimally invasive fetoscopic coverage for spina bifida aperta (SBA) was introduced in Poland in 2017. This study aims to present the results of the first patients that underwent this procedure in the 1st Department of Obstetrics and Gynecology, Medical University of Warsaw and compare them with the results obtained in other studies. Methods: We reviewed our data of 38 expectant mothers whose fetuses with SBA and normal karyotype underwent minimally invasive fetoscopic coverage at our center between September 2017 and February 2022. All procedures were carried out between 24 + 4 and 28 + 1 weeks of gestation employing general materno-fetal anesthesia. New methods were implemented with time, moving from the patch technique to the skin-to-skin technique suture. The results of the study were compared with the available literature on fetoscopic and open surgeries. Results: In total, the procedure was attempted 38 times and completed in 34 cases. All lesions were lumbar, and the median width of the lateral ventricle was 12 mm (6-17 mm). The median age at surgery was 26 weeks and the median age at delivery was 32 weeks of gestation (26.1-37.5). The average birth weight was 1870 g (1070-3350g). From 34 patients to 31 at the one year follow-up, 13 out of 31 (41.9%) babies needed a shunt and more than 70% of babies had a functional motor level that was the same or better than the anatomical level. Conclusions: Minimally invasive surgery for SBA could successfully be implemented following a tailored curriculum at our university with encouraging maternal and neonatal outcomes. The fetoscopic approach permits the assessment of various closure approaches. Preterm delivery is common but usually occurs beyond 30 weeks of gestation. At this time relevant complications from prematurity are rare.
Gesehen am 08.01.2026